2022
DOI: 10.31817/vjas.2022.5.4.03
|View full text |Cite
|
Sign up to set email alerts
|

Additive and Dominance Effects of MC4R and PIT1 Polymorphisms on Production and Carcass Traits in Duroc Pigs

Abstract: This study aimed to estimate the allelic and genotypic frequencies of single nucleotide polymorphisms (SNPs) of MC4R (melanocortin-4-receptor gene) and PIT1 (pituitary specific transcription factor-1) genes, and their additive dominance genetic effects on production and carcass traits in Duroc pigs. A total of 2170 tail tissue samples (1728 gilts and 442 male pigs) were collected from Dabaco Nucleus Breeding Pig Company, Bac Ninh province, Vietnam from January 2017 to June 2020. Polymorphisms in the MC4R and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(23 reference statements)
0
0
0
Order By: Relevance
“…Both nongenetic factors, such as pig feeding system (Lebret, 2008;Bankovska et al, 2020) or environmental temperature (Vashchenko & Berezovskyi, 2021) and genetic factors, such as MC4R genotype (Kim et al, 2000;Fan et al, 2009;Loos & Yeo, 2022), influence the intensity of growth and deposition of backfat. Unlike the human melanocortin-4-receptor gene, for which many polymorphic variants have been described, some of which are associated with appetite and obesity (Crovesy & Rosado, 2019;Chiurazzi et al, 2020;Mahmoud et al, 2022), very few polymorphic variants of the MC4R gene have been found in pigs (Fan et al, 2009;Llambí et al, 2020;Bo et al, 2022). A large number of scientists consider p.Asp298Asn to be the most practical melanocortin-4-receptor gene polymorphism (Fan et al, 2009;Gondim et al, 2019;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Both nongenetic factors, such as pig feeding system (Lebret, 2008;Bankovska et al, 2020) or environmental temperature (Vashchenko & Berezovskyi, 2021) and genetic factors, such as MC4R genotype (Kim et al, 2000;Fan et al, 2009;Loos & Yeo, 2022), influence the intensity of growth and deposition of backfat. Unlike the human melanocortin-4-receptor gene, for which many polymorphic variants have been described, some of which are associated with appetite and obesity (Crovesy & Rosado, 2019;Chiurazzi et al, 2020;Mahmoud et al, 2022), very few polymorphic variants of the MC4R gene have been found in pigs (Fan et al, 2009;Llambí et al, 2020;Bo et al, 2022). A large number of scientists consider p.Asp298Asn to be the most practical melanocortin-4-receptor gene polymorphism (Fan et al, 2009;Gondim et al, 2019;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%